Zooplankton assemblages from a tidal channel in the Bahía Blanca Estuary, Argentina - Hoffmeyer, Monica Susana (2007)
In this study we investigate for the first time the zooplankton assemblages in a relatively small tidal channel called Bahía del Medio, situated in the middle-outer area of the Bahía Blanca Estuary, South of the Main channel. We focused the study on micro- and mesozooplankton assemblages with emphasis on tintinnids, copepods and meroplankton along the annual cycle 1997-1998. Fifteen species of tintinnids belonging to 6 genera were observed in the study area, the mean total tintinnid abundance fluctuating between 3.4 x 106 ind. m-3 and 5.1 x 106 ind m-3. The mesozooplankton comprised 11 taxa, total abundance fluctuating between 449 ind m-3 in March 1997 and only 1 ind m-3 in October 1997. The channel proved to be spatially homogeneous in its physical and biochemical features. Micro- and mesozooplankton abundance displayed a high degree of spatial homogeneity, though the seasonal variation in both environment and zooplankton was significant. Comparison with the zooplankton observed at a station in the Main channel of the estuary showed differences in number of taxa represented, a general lower abundance of both assemblages and the presence of some rare species, a fact which is discussed.